Dengue Virus Infection of Blood–Brain Barrier Cells: Consequences of Severe Disease - Calderón-Peláez, María-Angélica; Velandia-Romero, Myriam L.; Bastidas-Legarda, Leidy Y.; Beltrán, Edgar O.; Camacho-Ortega, Sigrid J.; Castellanos, Jaime E. (Frontiers in Microbiology, 2019)
More than 500 million people worldwide are infected each year by any of the four dengue virus (DENV) serotypes. The clinical spectrum caused during these infections is wide and some patients may develop neurological alterations during or after the infection, which could be explained by the cryptic neurotropic and neurovirulent features of flaviviruses like DENV. Using in vivo and in vitro models, researchers have demonstrated that DENV can affect the cells from the blood-brain barrier (BBB) in several ways, which could result in brain tissue damage, neuronal loss, glial activation, tissue inflammation and hemorrhages. The latter suggests that BBB may be compromised during infection; however it is not clear whether the damage is due to the infection per se or to the local and/or systemic inflammatory response established or activated by the BBB cells. Similarly, the kinetics and cascade of events that trigger tissue damage, and the cells that initiate it, are unknown. This review presents evidence of the BBB cell infection with DENV and the response established towards it by these cells; it also describes the consequences of this response on the nervous tissue and compares these evidence with the one reported with neurotropic viruses of the Flaviviridae family. This information will allow us to understand more about the complex disease known as dengue, and its impact on a specialized and delicate tissue like is the nervous tissue.